Pembuktian Surat Dakwaan Mengenai Tindak Pidana Penghinaan (Pencemaran Nama Baik) yang Diatur dalam Pasal 310 Ayat 1 KUH Pidana Dihubungkan dengan Undang-Undang No. 40 Tahun 1999 Tentang Pers - Kusyana Kusyana (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2025)
The law enforcement process is a continuous activity carried out by the apparatus (officers) according to the needs of the law, where law enforcement must be fair and impartial. The issue of law enforcement in Indonesia is a complex issue, where one is very closely related to another. The 1945 Constitution states that the Republic of Indonesia is a state of law, not a state of power. Defendant KSY, S.E. BIN GANI on Sunday, January 27, 2002 at approximately 10:00 WIB or at least at a certain time in January 2002, located in the Indramayu area or at least in another place that is still included in the jurisdiction of the District Court, intentionally attacked the honor or good name of another person, namely the victim witness SUBIYANTO BIN SUTARA. The act was carried out by disseminating the show openly or by attaching writing or pictures, to a civil servant during or in carrying out his duties legally, which act was carried out in the following manner: At the time and place as mentioned above, initially the Defendant from January 21, 2002 until he made a picture of the victim witness and a writing entitled "KEPALA MARKET BANGKIR AROGAN" through the Jakarta Weekly Tabloid "Ambisi" published in Edition Number 63/Th III dated January 21-27, 2002 which was addressed to the victim witness as the Head of Bangkir Market, due to The news was broadcast and known to the public and the victim witness did not accept it and then reported it to the authorities. As a result of his actions, the Defendant is regulated and threatened with criminal penalties in Article; 310 paragraph (1) in conjunction with Article 316 of the Criminal Code. If we look at the issue of whether Mr. KSY, SE Bin Gani has clearly committed defamation? legally it is proven. However, because in the teachings of criminal law a person is considered to have committed a crime, it must be seen whether there is an intention or will from that person. If it turns out that the intention/will does not exist, then the criminal act is also considered not to exist. In this case, Mr. KSY, S.E BIN GANI did not have the intention or intent and purpose to insult or defame the good name or honor in his capacity as a civil servant with the position of head of the Bangjkir market. This is in accordance with the teachings of the law. Criminal law states that a crime must be based on subjective elements and objective elements. One of the subjective elements is that this crime must have an element of intent. Based on the Press Law (Law No. 40 of 1999) regulates the principles, provisions, and rights of press organizers in Indonesia, guarantees press freedom and affirms the role of the press as a pillar of democracy.